The Analysis Of Stress Management At Pt. Surya Wira Abadi Tribuana - Naufal Wiratama, Abid; Christian Wiradendi Wolor; Marsofiyati (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2025)
This study aims to analyze stress management among employees at PT. Surya Wira Abadi Tribuana. A descriptive qualitative approach was employed, involving data collection through semi-structured interviews with four employees from different divisions and workplace observation. The results indicate that most employees experience moderate to high levels of stress due to a heavy workload, tight deadlines, and pressure from superiors. The company has implemented stress management strategies, such as outings, group exercise, and team lunches, which are considered quite effective by some employees. However, some employees feel that these strategies are not fully effective and desire improved communication and support from management. This study recommends that the company enhance two-way communication, provide emotional and mental support, invest in adequate work facilities, and organize more bonding activities to strengthen relationships among employees.